Epidemiological profile of elderly people hospitalized due to stroke (Research, Society and Development, 2023)
Factors such as a sedentary lifestyle, high-calorie diet, alcohol consumption and smoking lead to excess weight, systemic arterial hypertension, diabetes mellitus and dyslipidemia. Among the main complications resulting from comorbidities, cerebrovascular accident (CVA) stands out, conceptualized as the interruption of the blood supply, due to an extravasation or obstruction of the vessel. In the meantime, welcoming with risk classification is one of the potentially decisive interventions, based on the assumption of effective care. Given the above, the guiding question arose: What is the epidemiological profile of elderly people hospitalized with stroke? This is an observational and descriptive epidemiological research, based on a historical series, with a quantitative approach. The information was collected between the months of October and December 2022 through a search in the Ministry of Health database, DATASUS-TABNET. Initially, the criterion “ICD-10 morb list” was selected in the “available selections” tab, indicating the search for the descriptor “stroke”. Searches were carried out always considering the year of care, with a new procedure being carried out for each desired variable, such as total hospitalizations, age group and gender. The data are relevant to provide an overview of epidemiological behavior, risk factors that may be related to morbidity and mortality, and public hospital spending on this neurological dysfunction. Preventive measures targeted to the circumstances are necessary because through the individualization of local realities it is possible to effectively approach the complex local network, advocating even more notoriety as a major challenge to public health.